2010
DOI: 10.1097/pcc.0b013e3181e8f502
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hypoglycemia and mortality in critically ill children*

Abstract: Hypoglycemia is common in critically ill children. It is associated with increased mortality rates in critically ill nondiabetic children. Our data suggest that hypoglycemia is also associated with worsening organ function. Hypoglycemia may merely be a marker of severity of illness. Further investigations are needed to establish the mortality risk with hypoglycemia due to insulin compared to spontaneous hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
68
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 50 publications
3
68
0
1
Order By: Relevance
“…Hypoglycemia is common in critically ill children and is associated with increased mortality rates in critically ill nondiabetic children (Faustino andBogue, Cornblath andIchord, 2000, Reid andLosek, 2005). A recent study by Faustino et al showed that hypoglycemia was associated with worsening organ function (Faustino and Bogue) and concluded that it may be a marker of severity of illness.…”
Section: Associated Factors Of Hypoglycemiamentioning
confidence: 99%
“…Hypoglycemia is common in critically ill children and is associated with increased mortality rates in critically ill nondiabetic children (Faustino andBogue, Cornblath andIchord, 2000, Reid andLosek, 2005). A recent study by Faustino et al showed that hypoglycemia was associated with worsening organ function (Faustino and Bogue) and concluded that it may be a marker of severity of illness.…”
Section: Associated Factors Of Hypoglycemiamentioning
confidence: 99%
“…13 Pediatric intensivists indicated that safe adjustment of continuous intravenous insulin to minimize the risk of hypoglycemia was crucial. 10,11,13 Thus, the current Heart and Lung Failure-Pediatric Insulin Titration (HALF-PINT) trial tested the hypothesis that tight glycemic control to a target range of 80 to 110 mg per deciliter (lower target) versus a target range of 150 to 180 mg per deciliter (8.3 to 10.0 mmol per liter; higher target) would increase the number of intensive care unit (ICU)-free days in critically ill children with hyperglycemia who have cardiovascular or respiratory failure; the trial targeted an enriched cohort of pediatric patients in the ICU who could benefit most from tight glucose control -those with the greatest risk of death and longest lengths of stay. 14,15 Continuous glucose monitoring and computer-guided insulin adjustment were used to minimize hypoglycemia.…”
mentioning
confidence: 99%
“…[2][3][4] Results of trials of tight glycemic control in critically ill children have been inconsistent [5][6][7][8] ; retrospective studies have consistently shown an association between hyperglycemia and poor outcomes. [9][10][11][12] A single-center, randomized trial involving children, most of whom had undergone cardiac surgery, showed significantly lower mortality and infection rate and shorter length of stay with lower glucose targets than with higher glucose targets, despite high rates of severe hypoglycemia (blood glucose level, <40 mg per deciliter [2.2 mmol per liter]). 5 Other investigators found significantly lower morbidity with lower glucose targets than with higher glucose targets in pediatric patients with burns.…”
mentioning
confidence: 99%
“…11 Of utmost importance to appropriate BG control is the demonstration of a safe, feasible, and practical method for minimizing hypoglycemia. [11][12][13] In the adult intensive care unit (ICU), the use of computer clinical decision support (CDS) for BG control results in more consistent BG target levels and fewer adverse events than do paper protocols. [14][15][16] To optimize BG control, investigators have implemented bedside paper protocols or guidelines for intravenous insulin titration in the pediatric ICU (PICU).…”
mentioning
confidence: 99%